Redox initiation system-based timing free radical polymerization method and hydrogel

Through the timed free radical polymerization method based on the redox initiation system, the problems of complex hydrogel preparation process and poor performance are solved, and the hydrogel preparation with high stability and compressive elasticity are achieved. It is suitable for industrial production and phase with liquid crystals. Allow.

CN119505077APending Publication Date: 2025-02-25SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460984.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing hydrogel preparation process is complex and uncontrollable, with low polymerization efficiency and poor hydrogel performance, which cannot meet the needs of industrial use, especially for anisotropic hydrogels, which lacks a highly compatible polymerization system.

Method used

The timed radical polymerization method based on the redox initiation system is adopted. By mixing the reaction solvent, polymerization monomer, crosslinking agent and reducing agent evenly, removing oxygen, adding an oxidant, controlling the specific time to start the polymerization reaction to form a hydrogel. This method can adjust the polymerization start time by regulating the initiator ratio to achieve timed polymerization, and is suitable for emulsion polymerization of a variety of water-soluble electron-deficient vinyl monomers.

Benefits of technology

It realizes high structural stability, good compression elasticity and shape recovery ability of hydrogel. It is suitable for industrial production and is compatible with liquid crystals and does not destroy the liquid crystal structure. It can achieve a variety of anisotropy at room temperature and light-proof. Preparation of hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505077A_ABST
    Figure CN119505077A_ABST
Patent Text Reader

Abstract

The invention discloses a timed free radical polymerization method based on a redox initiation system and hydrogel. The method comprises the following steps: uniformly mixing a reaction solvent, a polymerization monomer, a cross-linking agent and a reducing agent; inert gas is introduced into the mixture to remove oxygen, then an oxidizing agent is added, uniform mixing is performed, standing is performed, a polymerization reaction is started after specific time, hydrogel is formed, and the specific time is related to the molar ratio of the reducing agent to the oxidizing agent. The method is mild in reaction, high in controllability and uniform and controllable in cross-linking, and the prepared hydrogel has high structural stability and good compression resistance elasticity and shape recovery capacity and can be used as a universal method for industrial production of the hydrogel; the ionic strength of the system is low, the microcosmic assembly structure of the colloid is not damaged, and the preparation of anisotropic hydrogel such as liquid crystal composite hydrogel can be realized in the dark at normal temperature; the polymerization starting time is adjustable, the hardness of the hydrogel is controllable, and different requirements for emulsion polymerization time and gel performance in the industry are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of gel polymerization, and specifically relates to a timed free radical polymerization method and a hydrogel based on a redox initiation system. Background Art

[0002] Hydrogels are three-dimensional networks formed by hydrophilic polymer chains through physical or chemical crosslinking and are widely used in many fields. Emulsion polymerization of monomers is an important way to prepare hydrogels through chemical crosslinking, which can be completed through different initiation systems, such as photoinitiator system, thermal initiator system, redox initiator system, etc. Among them, the redox initiator system generates intermediate free radicals through electron transfer reaction, and the activation energy is greatly reduced, which can achieve room temperature polymerization, and at the same time improve the initiator decomposition rate and reaction rate. The selection of the initiator system is very important. At present, the preparation of hydrogels often has problems such as complex and uncontrollable process, low polymerization efficiency, poor hydrogel performance, and inability to meet the use. Different initiator systems often affect the polymerization effect and reaction characteristics of hydrogels. For the polymerization of anisotropic hydrogels such as liquid crystals, they often face problems such as destruction of self-assembly structure and failure of gelation, and a compatible initiator system must be selected. An initiator system with high stability, good compatibility with other substances, strong controllability, and applicable to the polymerization of a variety of monomers is more suitable for industrial large-scale preparation of hydrogels. Summary of the invention

[0003] The purpose of the present application is to provide a timed free radical polymerization method and hydrogel based on a redox initiation system. The hydrogel prepared by a simple process has a uniform cross-linked structure, high stability in structure and performance, and good compressive elasticity, so as to solve the problems in the prior art of hydrogel preparation, such as complex and uncontrollable process, low polymerization efficiency, poor hydrogel performance, inability to meet the use requirements, and lack of a highly compatible polymerization system for some anisotropic hydrogels.

[0004] In order to achieve the above-mentioned object, the first aspect of the present application provides a timed free radical polymerization method based on a redox initiation system, comprising:

[0005] Mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the reducing agent uniformly to obtain a mixture;

[0006] Inert gas is introduced into the mixture to remove oxygen, and then an oxidant is added and mixed evenly and then allowed to stand. After a specific time, polymerization reaction begins to form a hydrogel, and the specific time is related to the molar ratio of the reducing agent to the oxidizing agent.

[0007] In one or more embodiments, the reducing agent is thiourea, the oxidizing agent is tert-butyl hydroperoxide, and the reaction solvent is water or liquid crystal.

[0008] In one or more embodiments, the liquid crystal includes one or more combinations of graphene oxide liquid crystal, cellulose liquid crystal, chitosan liquid crystal, and chitosan liquid crystal.

[0009] In one or more embodiments, before the step of uniformly mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the reducing agent, the step further includes:

[0010] Confirm the reaction temperature, the concentration of the polymerization monomer, and the concentration of thiourea or tert-butyl hydroperoxide;

[0011] Constructing a model for describing the mapping relationship between the molar ratio of thiourea to tert-butyl hydroperoxide and the polymerization start time at a target reaction temperature and a target amount of polymerization monomer;

[0012] The expected polymerization start time is input into the model to obtain the target molar ratio of thiourea to tert-butyl hydroperoxide, and then the reaction solvent, polymerization monomer, crosslinking agent, thiourea and tert-butyl hydroperoxide are weighed in proportion.

[0013] In one or more embodiments, the mapping relationship includes: when the molar ratio of thiourea to tert-butyl hydroperoxide varies between 0.13 and 2.55, the molar ratio of thiourea to tert-butyl hydroperoxide is negatively correlated with the polymerization start time.

[0014] In one or more embodiments, the reaction temperature is room temperature, the molar concentration of the polymerization monomer is 1.41 mol / L, the molar concentration of tert-butyl hydroperoxide is 30.96 mmol / L, and the mapping relationship includes: when the molar ratio of thiourea to tert-butyl hydroperoxide increases linearly from 0.13 to 2.55, the polymerization start time is linearly shortened from 83 min to 2 min.

[0015] In one or more embodiments, the step of uniformly mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the thiourea is specifically as follows:

[0016] The reaction solvent, polymerization monomer, cross-linking agent and thiourea were vortexed and mixed evenly, and then the bubbles were removed by ultrasonication.

[0017] In one or more embodiments, the inert gas is nitrogen or argon, and the inert gas is introduced for 0.5 to 1.5 minutes.

[0018] In order to achieve the above-mentioned purpose, the second aspect of the present application provides a hydrogel prepared by the timed free radical polymerization method described in any of the above-mentioned embodiments.

[0019] In one or more embodiments, the hardness of the hydrogel is inversely proportional to the polymerization start time.

[0020] In one or more embodiments, the reaction solvent is liquid crystal, the hydrogel exhibits an anisotropic ordered structure of liquid crystal, and the liquid crystal structure is completely retained in the polymer matrix.

[0021] Different from the prior art, the beneficial effects of this application are:

[0022] The timed free radical polymerization method of the present application has mild reaction, high controllability, high polymerization initiation efficiency, uniform and controllable cross-linking, and the prepared hydrogel has high structural stability, good compressive elasticity and shape recovery ability, and can be used as a general method for industrial production of hydrogels;

[0023] The initiation system of the present application has high compatibility, does not destroy the liquid crystal structure, and can realize the preparation of various anisotropic hydrogels such as liquid crystal composite hydrogels in the dark and at room temperature;

[0024] The free radical polymerization method of the present application can adjust the polymerization start time by regulating the initiator ratio to achieve timed polymerization, and the hardness of the hydrogel is adjustable, which can meet the different requirements of the industry for emulsion polymerization time and gel performance;

[0025] The free radical polymerization method of the present application is applicable to the emulsion polymerization of various water-soluble electron-deficient vinyl monomers. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a schematic flow chart of an implementation method of a timed free radical polymerization method based on a redox initiation system of the present application;

[0028] Figure 2 is a characterization diagram of the polyacrylamide hydrogel prepared in Example 1 of the present application;

[0029] Figure 3 This is a graph showing the hydrogel test results of Example 2 of the present application;

[0030] Figure 4 This is a characterization diagram of the liquid crystal composite hydrogel prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0032] Thiourea is an organic sulfur-containing compound with stable physicochemical properties. It is soluble in water and alcoholic organic solvents. It contains a large number of free electrons in its own molecules and can provide electrons to other substances. It has weak reducing properties and is an excellent water-soluble non-ionic reducing agent. In the polymerization of hydrogel monomers, the redox initiation system based on thiourea has not been widely studied and applied. The more typical one is the hydrogen peroxide-thiourea polymerization system, both of which are non-ionic water-soluble initiators. When hydrogen peroxide reacts with thiourea, hydrogen peroxide is reduced to water and thiourea is oxidized to disulfide (CS 2 ) and ammonia (NH 3 ), a large amount of heat is released during the reaction, and the reaction rate is affected by temperature, pH, initiator concentration, etc. In the hydrogen peroxide-thiourea redox initiation system, since hydrogen peroxide has strong oxidizing properties and the reaction is highly uncontrollable, when the oxidant content is high, the reaction is violently exothermic. Explosive polymerization occurs, so that the generated polyacrylamide cannot be completely grown into a macromolecular chain, and the uncontrollable temperature caused by the heat release during the reaction makes it difficult to control the reaction rate and polymerization time during the polymerization process. Therefore, the initiation efficiency and result reproducibility of the hydrogen peroxide system are poor, and it is now rarely used for industrial-scale polymerization.

[0033] In order to solve the problems of complicated and uncontrollable process, low polymerization efficiency, poor performance of hydrogel, inability to meet the use, and lack of high compatibility polymerization system of anisotropic hydrogel in the preparation of hydrogel at present, the applicant has adopted a timed non-ionic redox free radical polymerization method to prepare a variety of stable, simple, anisotropic hydrogels at room temperature and in the dark, with thiourea as the reducing agent and tert-butyl hydroperoxide as the oxidant. As an organic peroxide, tert-butyl hydroperoxide is a rare non-ionic water-soluble initiator in the organic peroxide class, and its reaction is relatively mild and more compatible with other substances. The tert-butyl hydroperoxide-thiourea redox initiation system formed after adding thiourea has strong stability and controllability, and breaks the limitation of light or temperature of photo-initiated polymerization or thermal polymerization, and can be directly polymerized at room temperature and in a lightless environment, with a wider range of applications.

[0034] Specifically, see Figure 1 , Figure 1 It is a schematic flow chart of an implementation method of a timed free radical polymerization method based on a redox initiation system of the present application.

[0035] like Figure 1 As shown, the polymerization method includes:

[0036] S100, mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the reducing agent uniformly to obtain a mixture.

[0037] In one embodiment, the reducing agent may be thiourea.

[0038] In one embodiment, the polymerizable monomer may be various water-soluble electron-deficient vinyl monomers, such as acrylamide, N-polyacrylamide, acrylic acid, methacrylic acid, etc. Correspondingly, the cross-linking agent may be a cross-linking agent that matches the above-mentioned polymerizable monomers. For example, when the polymerizable monomer is acrylamide, the cross-linking agent may be an acrylamide cross-linking agent, such as N,N-methylenebisacrylamide. Those skilled in the art may select the cross-linking agent and adjust its concentration based on the actual polymerizable monomer, and the effects of the present embodiment can be achieved.

[0039] S200, an inert gas is introduced into the mixture to remove oxygen, and then an oxidant is added and mixed evenly and then allowed to stand. After a specific period of time, a polymerization reaction begins to form a hydrogel.

[0040] In one embodiment, the inert gas may be nitrogen or argon, and the inert gas may be introduced for 0.5 to 1.5 minutes to remove oxygen.

[0041] In one embodiment, the reaction solvent can be water, thereby polymerizing to prepare a hydrogel; since the reaction system of the present application has a low ionic strength and is highly compatible with other substances, the colloidal microassembly structure will not be destroyed during the reaction. Therefore, in another embodiment, the reaction solvent can also be a liquid crystal, such as graphene oxide liquid crystal, cellulose liquid crystal, chitin liquid crystal, etc., to prepare a liquid crystal composite hydrogel.

[0042] Since the preparation method of the present application breaks the restrictions of photo-initiated polymerization or thermal polymerization on light or temperature, in one embodiment, the above-mentioned polymerization reaction can be carried out at room temperature and in a light-free environment.

[0043] Wherein, the specific time is associated with the molar ratio of the reducing agent and the oxidizing agent. In the thiourea-tert-butyl hydroperoxide reaction system used in the present application, the molar ratio of thiourea and tert-butyl hydroperoxide is linearly related to the polymerization start time. When other reaction conditions remain unchanged and the concentration of tert-butyl hydroperoxide in the reaction system remains unchanged, as the concentration of thiourea increases, the polymerization start time gradually shortens. Therefore, the timed polymerization can be achieved by adjusting the molar ratio of thiourea and tert-butyl hydroperoxide. In addition, when the molar ratio of thiourea and tert-butyl hydroperoxide changes, the hardness of the hydrogel also changes accordingly. The hardness of the hydrogel can be regulated by adjusting the molar ratio of thiourea and tert-butyl hydroperoxide to meet the different requirements for emulsion polymerization time and gel performance in industry. The hydrogel can be prepared by timed polymerization at room temperature and in a light-proof environment.

[0044] Based on the above rule that the molar ratio of thiourea to tert-butyl hydroperoxide is linearly correlated with the polymerization start time, the preparation method of the present application may further include:

[0045] Confirm the reaction temperature, the concentration of the polymerization monomer, and the concentration of thiourea or tert-butyl hydroperoxide;

[0046] A model is constructed, and the model is used to describe the mapping relationship between the molar ratio of thiourea and tert-butyl hydroperoxide and the polymerization start time under the target reaction temperature and the target amount of polymerization monomer;

[0047] The expected polymerization start time is input into the model to obtain the target molar ratio of thiourea and tert-butyl hydroperoxide, and then the reaction solvent, polymerization monomer, cross-linking agent, thiourea and tert-butyl hydroperoxide are weighed in proportion.

[0048] Among them, the model can be obtained by a fitting method based on the polymerization start time data corresponding to different molar ratios, or by a machine learning neural network method. By inputting the expected polymerization start time into the model, the target molar ratio can be obtained, thereby achieving the purpose of timed polymerization.

[0049] The effects of the technical solution of this application are described in detail below in conjunction with specific embodiments:

[0050] Example 1: Polyacrylamide hydrogel preparation experiment

[0051] Take 1000 μL of deionized water, add 100 mg of acrylamide, 10 mg of N,N-methylenebisacrylamide and different proportions of thiourea in turn, vortex mix evenly, ultrasonicate for 5 minutes, and pass nitrogen into the mixture for 1 minute to remove oxygen. Then add 3 μL of tert-butyl hydroperoxide, mix evenly and keep it at room temperature. The hydrogel is obtained by redox polymerization. The prepared hydrogel is characterized and obtained. Figure 2 .

[0052] See also Figure 2 , Figure 2 This is a characterization diagram of the polyacrylamide hydrogel prepared in Example 1 of the present application. In the figure, a is a photo before polymerization, b and c are photos after polymerization, d and e are SEM photos of the hydrogel after polymerization, and the upper right corner of d is a photo of the hydrogel.

[0053] As shown in the figure, the redox free radical reaction between the initiators promotes the cross-linking of acrylamide to form high molecular weight polyacrylamide. After polymerization, the solution loses fluidity and undergoes a gelation transition from liquid to gel, such as Figure 2 As shown in Figure c, the colorless solution polymerizes into a solid white hydrogel, which can maintain its shape after being inverted. The hydrogel is placed in an oven for drying at 60°C for 24 hours, then taken out and broken into small pieces by hand. The cross section of the hydrogel is sprayed with gold at a current of 30 mA for 1 minute. Figure 2 As shown in d and e, the gel obtained after the polymerization is intact in appearance, without cracks or damage. The voltage of the scanning electron microscope is set to 5 kV and the current is 5 μA. It shows a dense three-dimensional network structure under the scanning electron microscope, which proves that it is highly cross-linked and has a stable and uniform network structure. It can be seen that the gel product obtained by the polymerization of monomers initiated by tert-butyl hydroperoxide and thiourea has good structural stability and excellent polymerization effect.

[0054] Example 2: Timed polymerization experiment

[0055] Ten groups of experiments were designed. 1000 μL of deionized water, 100 mg of acrylamide and 10 mg of N,N-methylenebisacrylamide were fixedly added to each group. Different amounts of thiourea were added to each group and vortexed to mix evenly. After ultrasonication for 5 minutes, nitrogen was passed into the mixture for 1 minute to remove oxygen. Then, the same amount of tert-butyl hydroperoxide was added to each group. After mixing evenly, the mixture was allowed to stand at room temperature and in the dark to start the polymerization reaction, and the polymerization start time was recorded.

[0056] Please refer to the table below for the concentrations of thiourea and tert-butyl hydroperoxide in each group, as well as the polymerization start time.

[0057]

[0058] As shown in the above data, when the concentration of thiourea gradually increases, the polymerization start time gradually decreases. Specifically, when the molar ratio of thiourea to tert-butyl hydroperoxide increases linearly from 0.13 to 2.55, the polymerization start time is linearly shortened from 83 min to 2 min. Based on the above data, a model can be constructed to describe the mapping relationship between the molar ratio of thiourea to tert-butyl hydroperoxide and the polymerization start time, so as to select thiourea and tert-butyl hydroperoxide with corresponding concentrations for the target polymerization start time to achieve the purpose of timed polymerization.

[0059] From the perspective of reaction mechanism, the single electron transfer between tert-butyl hydroperoxide and thiourea causes a redox reaction to generate free radicals, which can initiate monomer polymerization at a relatively low temperature. The addition of thiourea reduces the decomposition activation energy of tert-butyl hydroperoxide, increases its decomposition rate, and thus increases the polymerization rate. In addition, the two initiators have stable physicochemical properties, mild chemical reactions, and strong controllability. By simply changing the amount of thiourea added, the polymerization rate can be effectively regulated to obtain products that polymerize at different times, thereby achieving timed polymerization of the hydrogel. Under the premise of an appropriate oxidant concentration, when the reducing agent concentration is small, increasing the reducing agent ratio can significantly shorten the polymerization start time. When the reducing agent concentration is close to or even exceeds the amount of oxidant added, the polymerization start time is basically maintained within 5 minutes, and short-time polymerization can be achieved.

[0060] It should be noted that the amount of reducing agent added should not be too much or too little. When too much reducing agent is added to the system, the side effects between the reducing agent and the oxidizing agent will inhibit the polymerization reaction, have a negative effect on the start time of the polymerization, and are not conducive to the complete cross-linking reaction; if the reducing agent is too little, it will not be able to accelerate the polymerization reaction as it should, and the polymerization effect will be more easily affected by the oxygen content in the air and deteriorate, thereby affecting the performance of the hydrogel.

[0061] At the same time, the polymerization time of the hydrogel is also affected by factors such as temperature and oxygen content. The polymerization start time corresponding to the initiator ratio in the above table is limited to a reference value obtained under the conditions of Example 2. There are certain changes in different scene experiments. Those skilled in the art can obtain the corresponding polymerization start time under the required conditions based on the actual polymerization scene records and construct a mapping relationship model. Under the condition of keeping the initiator ratio unchanged, the polymerization start time can be further regulated by adjusting the temperature, the polymerization can be accelerated by increasing the temperature, and the polymerization can be delayed by cooling.

[0062] In order to verify the above model, the above groups 2, 3, and 6 were selected, and in situ redox polymerization was carried out using a rheometer in a dark environment at room temperature. The polymerization start time was further determined by the storage modulus, and an in situ full-frequency scan was performed after the polymerization was completed to evaluate the mechanical stability of the hydrogel. Afterwards, the hydrogel was further subjected to a compression test at a compression rate of 1 mm / min.

[0063] Please refer to the above test results Figure 3 , Figure 3 This is a graph of the hydrogel test results in Example 2 of the present application, in which a is a curve of the storage modulus of the hydrogel changing with time, b is the storage modulus of the hydrogel at different scanning frequencies, c is the compression curve of the hydrogel, and d is a graph of the compression and shape recovery process of the hydrogel with a polymerization start time of 3730s.

[0064] like Figure 3As shown in a, the polymerization start time corresponds to the inflection point where the storage modulus changes with time curve increases sharply, which reflects the beginning of the elastic response in the hydrogel. The polymerization start times of the three groups of experiments are 575s, 1950s and 3730s, respectively, which match the data of the above model and realize timed polymerization.

[0065] like Figure 3 As shown in b, the storage modulus of the hydrogel remains stable at a frequency of 0.1-100 Hz and a strain of 1%. Among them, the storage modulus and hardness of the hydrogel with a polymerization start time of 575s are the highest. As the polymerization start time increases, the storage modulus and hardness of the hydrogel gradually decrease. As the molar ratio of thiourea and tert-butyl hydroperoxide increases, the polymerization start time shortens, and a gel with a higher storage modulus can be formed. This may be because the addition of the initiator helps the cross-linking reaction to occur and form a denser network structure. It can be seen that by simply adjusting the amount of reducing agent added, timed polymerization can be achieved in a light-proof and room temperature environment to obtain a hydrogel with a stable structure.

[0066] like Figure 3 As shown in c, the hydrogels with three polymerization start times did not show abnormal cracks and breakage during the entire compression test, and the compression curves were stable, confirming the stability of the internal cross-linked structure. Among them, the gel with a polymerization start time of 575s was harder, and the load required to generate strain was higher, and the structure collapsed at about 57% strain. As the polymerization start time increases, less reducing agent is added, and the hydrogel structure is looser and the gel is softer. The load required to achieve the same strain conditions is lower, and it can withstand greater compressive strains. The maximum compressive strain can reach 60% and above, and the compressive strength can reach up to about 180Kpa.

[0067] like Figure 3 As shown in (d), when the compression strain of the hydrogel with a polymerization start time of 3730s reaches 50%, the pressure is removed and the hydrogel can recover to its original shape, showing good elasticity and shape recovery ability.

[0068] As can be seen from the above, the system of the present application can induce a uniform and controllable cross-linking reaction, and the hydrogel product prepared by polymerization has a stable and uniform structure and good compressive elasticity, which meets the daily use requirements of the hydrogel. At the same time, by changing the ratio of the initiator, not only the polymerization start time can be regulated, but also the hardness of the hydrogel can be regulated. A high reducing agent concentration often results in a shorter polymerization start time and a harder hydrogel, while a low reducing agent concentration helps to obtain a longer polymerization start time and a softer hydrogel. The hardness of the hydrogel is inversely proportional to the time of the polymerization start reaction.

[0069] Example 3: Liquid crystal composite hydrogel preparation experiment

[0070] Graphene oxide liquid crystal and cellulose liquid crystal were used to replace the deionized water in Example 1, respectively, to polymerize to obtain anisotropic liquid crystal composite hydrogel, and the prepared hydrogel was cut into thin slices with a thickness of less than 1 mm, and observed and characterized under a polarizing microscope with two orthogonal polarizers to obtain Figure 4 .

[0071] See also Figure 4 , Figure 4 3 is a characterization diagram of the liquid crystal composite hydrogel prepared in Example 3 of the present application, in which a and b are characterization diagrams of the cellulose-polyacrylamide composite liquid crystal hydrogel obtained by polymerization, and the upper right corner of a is a photograph of the cellulose-polyacrylamide composite liquid crystal hydrogel, c and d are characterization diagrams of the graphene oxide-polyacrylamide composite hydrogel obtained by polymerization, and the upper right corner of c is a photograph of the graphene oxide-polyacrylamide composite hydrogel.

[0072] As shown in the figure, the liquid crystal structure of the liquid crystal composite hydrogel is retained, and the bright birefringence phenomenon unique to liquid crystals is clearly observed under a polarizing microscope in the hydrogel obtained by polymerization. Figure 4 ab can clearly observe a large number of typical ellipsoidal anisotropic liquid crystal droplets in cellulose liquid crystals. Figure 4 CD can observe locally oriented graphene oxide dispersion, showing the characteristics of nematic liquid crystal, which confirms that the polymerization system of the present application is compatible with a variety of liquid crystals, and its polymerization time controllability and structural stability are not affected by liquid crystal molecules, and can be used for room temperature, light-proof, and timed polymerization of high-performance anisotropic hydrogels.

[0073] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.

[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A timed free radical polymerization method based on a redox initiation system, characterized in that: include: Mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the reducing agent uniformly to obtain a mixture; Inert gas is introduced into the mixture to remove oxygen, and then an oxidant is added and mixed evenly and then allowed to stand. After a specific time, polymerization reaction begins to form a hydrogel, and the specific time is related to the molar ratio of the reducing agent to the oxidizing agent.

2. The timed free radical polymerization method according to claim 1, characterized in that: The reducing agent is thiourea, the oxidizing agent is tert-butyl hydroperoxide, and the reaction solvent is water or liquid crystal.

3. The timed free radical polymerization method according to claim 2, characterized in that: The liquid crystal includes one or more combinations of graphene oxide liquid crystal, cellulose liquid crystal and chitin liquid crystal.

4. The timed free radical polymerization method according to claim 2, characterized in that: Before the step of uniformly mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the reducing agent, the following steps are further included: Confirm the reaction temperature, the concentration of the polymerization monomer, and the concentration of thiourea or tert-butyl hydroperoxide; Constructing a model for describing the mapping relationship between the molar ratio of thiourea to tert-butyl hydroperoxide and the polymerization start time at a target reaction temperature and a target amount of polymerization monomer; The expected polymerization start time is input into the model to obtain the target molar ratio of thiourea to tert-butyl hydroperoxide, and then the reaction solvent, polymerization monomer, crosslinking agent, thiourea and tert-butyl hydroperoxide are weighed in proportion.

5. The timed free radical polymerization method according to claim 4, characterized in that: The mapping relationship includes: when the molar ratio of thiourea to tert-butyl hydroperoxide varies between 0.13 and 2.55, the molar ratio of thiourea to tert-butyl hydroperoxide is negatively correlated with the polymerization start time.

6. The timed free radical polymerization method according to claim 5, characterized in that: The reaction temperature is room temperature, the molar concentration of the polymerization monomer is 1.41 mol / L, the molar concentration of tert-butyl hydroperoxide is 30.96 mmol / L, and the mapping relationship includes: when the molar ratio of thiourea to tert-butyl hydroperoxide increases linearly from 0.13 to 2.55, the polymerization start time is linearly shortened from 83 min to 2 min.

7. The timed free radical polymerization method according to claim 1, characterized in that: The step of uniformly mixing the reaction solvent, the polymerization monomer, the cross-linking agent and the thiourea is specifically as follows: The reaction solvent, polymerization monomer, cross-linking agent and thiourea were vortexed and mixed evenly, and then the bubbles were removed by ultrasonication.

8. The timed free radical polymerization method according to claim 1, characterized in that: The inert gas is nitrogen or argon, and the inert gas is introduced for 0.5 to 1.5 minutes.

9. A hydrogel prepared by the timed free radical polymerization method according to any one of claims 1 to 8.

10. The hydrogel according to claim 9, characterized in that The hardness of the hydrogel is inversely proportional to the polymerization start time; and / or, The reaction solvent is liquid crystal, the hydrogel exhibits anisotropic ordered structure of liquid crystal, and the liquid crystal structure is completely retained in the polymer matrix.